Temperomandibular joint ankylosis in children - Perumal Jayavelu; S P Shrutha; G B Vinit (Wolters Kluwer Medknow Publications, 2014)
Temperomandibular joint (TMJ) ankylosis or hypo mobility involves fusion of the mandibular condyle to the base of the skull. Impairment of speech, difficulty in mastication, poor oral hygiene, rampant caries, and acute compromise of the airway pose a severe psychological burden on the tender minds of children. The treatment of TMJ ankylosis poses a significant challenge because of technical difficulties and a high incidence of recurrence. This report describes a case of 7-year-old with inability to open mouth, diagnosed with unilateral right bony TMJ ankylosis. The surgical approach consisted of inter-positional arthroplasty followed by physiotherapy. A detailed history, clinical and functional examination, and radiographic examination facilitating correct diagnosis followed by immediate surgical intervention and physiotherapy can help us to restore physical, psychological and emotional health of the child patient.